Nursing Care of Children with Hyperthermy in Typhoid Fever - Farida, Ana; Kurniawati, Kurniawati; Ani, Zuli; Fatehah, Alda (Jurnal Surya, 2022)
Introduction: Typhoid fever is an acute infectious disease that attacks the digestive tract caused by salmonella typhi bacteria, causing an increase in body temperature. This study aims to conduct a literature study of nursing care for children with typhoid fever.Methods: The research design uses a literature study with a case study of nursing care for children with typhoid fever in the Seruni pavilion room at the Jombang Hospital in 2016 and nursing care for children with typhoid fever with hyperthermia problems at the Waluya Malang Hospital in 2019 which includes assessment analysis, diagnosis determination, intervention, implementation, and evaluation in several research units.Results: The priority problem for clients with typhoid fever is hyperthermia. In respondents 1,3 and 4 after nursing actions for 3x24 hours the hyperthermia experienced by the client can be resolved. Meanwhile, in respondent 2 after nursing actions for 5x24 hours the hyperthermia experienced by the client can be resolved. Conclusion:In respondents 1, 3 and 4, the problem of hyperthermia can be resolved on the third day, while in respondent 2 the problem of hyperthermia can be resolved on the fifth day. As such, efforts are being made to prevent the occurrence of salmonella typhi bacterial infection, namely maintaining the food or drinks consumed and maintaining good environmental sanitation